MTA index: a simple 2D-method for assessing atrophy of the medial temporal lobe using clinically available neuroimaging - Menéndez-González, Manuel; López-Muñiz, Alfonso; Vega, José A.; Salas-Pacheco, José M.; Arias-Carrión, Oscar (Frontiers in Aging Neuroscience, 2014)
Background and purpose: Despite a strong correlation between severity of Alzheimer disease (AD) pathology and medial temporal lobe atrophy (MTA), its measurement has not been widely used in daily clinical practice as a criterion in the diagnosis of prodromal and probable AD. This is mainly because the methods available to date are sophisticated and difficult to implement for routine use in most hospitals. In this pilot study we aim to describe a novel, simple and objective method for measuring the rate of MTA in relation to the global atrophy using clinically available neuroimaging and describe the rationale behind this method. Description: This method consists of calculating a ratio of 3 regions traced manually on one single coronal MRI slide at the level of the interpeduncular fossa: i) the medial temporal lobe region (A); ii) the parenchyma within the medial temporal region, that includes the hippocampus and the parahippocampal gyrus -the fimbriae taenia and choroid plexus are excluded- (B); and iii) the body of the ipsilateral lateral ventricle (C). Therefore we can compute the ratio “Medial Temporal Atrophy index” at both sides as follows: MTAi = (A-B) x10/C. Conclusions: The MTAi is a simple 2D-method for measuring the relative extent of atrophy in the MTL in relation to the global brain atrophy. This method can be useful for a more accurate diagnosis of AD in routine clinical practice. Further studies are needed to assess the usefulness of MTAi in the diagnosis of early AD, in tracking the progression of AD and in the differential diagnosis of AD with other dementias.